Correlation between Knowledge, Attitudes, and Behaviour of Mothers about Exclusive Breastfeeding and Its Success Rate in Karangmulyo Village - Zulfihda, Alnaora Tanjinna; Setiyorini, Nurul; Himawan, Ari Budi; Arkhaesi, Nahwa (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Exclusive breastfeeding (ASI) is a condition when the baby only receives breast milk from his mother or foster mother for the first 6 months. The rate of exclusive breastfeeding is 37% worldwide and 54.1% in Jakarta. Infants who are not breastfed are associated with an increased incidence of infectious morbidity. Knowledge is one of the basic factors that determine a person's reaction and decision-making when faced with a situation. Knowledge will bring up a person's attitude to determines the behavior or action to be taken. Aim: To know the relationship between mother’s knowledge, attitudes, and behavior about exclusive breastfeeding with the level of success. Methods: Analytic observational study with a cross-sectional design conducted for 2 months in Karangmulyo Village, Kendal Regency, Central Java. The research subjects consisted of 66 mothers who had children aged 6-24 months. Assessment is carried out on the level of knowledge, attitudes, and behavior of mothers regarding exclusive breastfeeding, as well as the success rate of exclusive breastfeeding. Data analysis used the Mann-Whitney test, Chi-square, and Fischer exact. Significant p<0.05. Results: Most mothers have a good level of knowledge (n=57), attitude (n=45), and a sufficient level of behavior (n=64) regarding exclusive breastfeeding. There was no significant result in the level of knowledge (p=0.528; 0.820), attitude (p=0.339; 1.000), behaviour (p=0.342; 0.515) with the success of exclusive breastfeeding. Conclusion: There is no relationship between the level of knowledge, attitudes, and behavior on the success of exclusive breastfeeding.